World of waste: dilemmas of industrial development - Gourlay, K.A. (Zed Books Ltd. LondonGB, 1992)
Examines the production and disposal of waste. The author argues that continued industrial growth is threatened less by exhaustion of resources viz. fossil fuels than by failure to cope with the waste produced.